Spain - Facaros, Dana (Cadogan guides, 1996)
This fourth edition of Cadogan's bestselling guide has been comprehensively updated, and contains new maps and expanded practical information on the best places to stay, from mountain refufes to paradores, how to get around, festivals, and where to find the best paella, gazpacho or tapas.